The effect of intrauterine hypotrophy on the cardiovascular system of neonates - Gazy, Patrycja; Marciniak, Sylwia; Sławska, Helena; Olejek, Anita; Mazur, Bogdan (Pediatria Polska - Polish Journal of Paediatrics, 2019)
Intrauterine hypotrophy is an important, dangerous, and increasingly common complication of pregnancy. It is also the most common factor identified in cases of stillbirth. Intrauterine growth restriction plays a significant role in short- and long-term outcome and is associated with brain damage and neurodevelopmental impairment. Perinatal asphyxia is observed in 50% of the population of growth-restricted infants, who are also more prone to early complications such as intraventricular haemorrhage, necrotising enterocolitis, persistent pulmonary hypertension, hypoglycaemia, or hypothermia. There are also long-term consequences of intrauterine growth retardation, projecting into adult life, such as increased risk of cardiovascular disease, endocrine disorders, renal dysfunction, or metabolic syndrome. These observations are consistent with Barker’s hypothesis, now referred to as the “developmental origins of health and disease”. This article is a review of the literature regarding early and long-term complications as well as cardiovascular risk in this group of patients.